Harvest index in common bean - Costa, Joaquim Geraldo Cáprio da; Shibata, Josué Kohashi; Colin, Salvador Miranda (Pesquisa Agropecuaria Brasileira, 2014)
Using bean varieties Canário 107, a determinate bush type; Michoacan 12-A-3, an indeterminate short-vine, erect type; Negro 150 and Flor de Mayo X-16441, indeterminate climbing longvine types, the inclusion of total aerial material produced by bean plants during the growth period, in the calculation of the modified harvest index (Hlm = weight of seeds with 10% moisture/dry weight of all aerial parts produced during the plant cycle x 100) and the correlation of this index and the customary harvest index (Hlc = weight of seeds with 10% moisture/dry weight of aerial parts existent in harvest x 100) with seed yield were studied. Results indicated a closer relationship between modified harvest index with seed yield than between the customary harvest index and the seed yield. It might be assumed that modified harvest index is more an appropriate procedure to be used as an indirect index to yield.